2020
DOI: 10.1007/s10483-020-2644-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving control effects of absence seizures using single-pulse alternately resetting stimulation (SARS) of corticothalamic circuit

Abstract: Presently, we develop a simplified corticothalamic (SCT) model and propose a single-pulse alternately resetting stimulation (SARS) with sequentially applying anodic (A, “+”) or cathodic (C, “−”) phase pulses to the thalamic reticular (RE) nuclei, thalamus-cortex (TC) relay nuclei, and cortical excitatory (EX) neurons, respectively. Abatement effects of ACC-SARS of RE, TC, and EX for the 2Hz–4Hz spike and wave discharges (SWD) of absence seizures are then concerned. The m:n on-off ACC-SARS protocol is shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Besides, they also explored the possible sources of abnormal oscillations in the CTBG, and found that oscillations around 5 Hz and 20 Hz can be generated through a strong indirect way, which will also lead to increase the synchronization of the entire BG. In addition to exploring PD, the mean-field model of CTBG has also been widely used to explore neurological diseases such as epilepsy [38][39] . Subsequently, based on the mean-field model of CTBG, a new network model for the pedunculopontine nucleus (PPN) was established to investigate how PPN controls the PD through the projections from the PPN to several key nuclei of BG and thalamus [40] .…”
Section: Neural Field Modelsmentioning
confidence: 99%
“…Besides, they also explored the possible sources of abnormal oscillations in the CTBG, and found that oscillations around 5 Hz and 20 Hz can be generated through a strong indirect way, which will also lead to increase the synchronization of the entire BG. In addition to exploring PD, the mean-field model of CTBG has also been widely used to explore neurological diseases such as epilepsy [38][39] . Subsequently, based on the mean-field model of CTBG, a new network model for the pedunculopontine nucleus (PPN) was established to investigate how PPN controls the PD through the projections from the PPN to several key nuclei of BG and thalamus [40] .…”
Section: Neural Field Modelsmentioning
confidence: 99%
“…Introduction. Nonlinear dynamics has played very important roles in identifying dynamics of neural electrical activities [10,29,32], which are involved in the information processing, locomotion control, cognitive functions, and brain disease [8,19,31]. These activities mainly include the steady state such as the resting state and the firing behavior composed of action potentials or spikes, for example, the spiking and bursting, which has been widely investigated with the conceptions of bifurcations and chaos [6,16,18,23,33].…”
mentioning
confidence: 99%
“…Identification of nonlinear dynamics of neuronal electrical behavior is very important for understanding the functions of nervous system [1][2][3][4][5][6]. Neuronal bursting is a complex nonlinear electrical behavior related to fast and slow variables, which participates many kinds of physiological functions, pathological functions, and even brain diseases [7][8][9]. For example, bifurcations of bursting have been identified to participate information coding [10][11][12][13][14] in blood pressure and pathological pain.…”
Section: Introductionmentioning
confidence: 99%